Low-temperature printing conductive silver paste and preparation method thereof

By preparing modified polyurethane and functionalized polyurethane under low temperature conditions, and combining it with silver nitrate and silver powder to form a semi-interpenetrating grid structure, the problem of poor bending effect of low-temperature conductive silver paste is solved, and high conductivity and good mechanical properties are achieved.

CN119560211AActive Publication Date: 2025-03-04DONGGUAN DOMAL ELECTRONICS SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411565001.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-04
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

At this stage, the low-temperature conductive silver paste has poor bending effect, which affects normal use.

Method used

Modified polyurethane is prepared by reacting raw materials such as polyethylene glycol, modified monomer, isophorone diisocyanate and DMF under specific conditions, and reacting with aniline to form functionalized polyurethane, combining silver nitrate and silver powder to form a stable conductive pathway and semi-interpenetrating grid structure, improving mechanical properties.

Benefits of technology

The high conductivity and good bending resistance of low-temperature printed conductive silver paste are achieved, ensuring the stability and performance of conductive silver paste in use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-temperature printing conductive silver paste and a preparation method thereof, and the conductive silver paste comprises the following raw materials in parts by weight: 10-15 parts of functionalized polyurethane, 3-5 parts of 1, 6-hexanediol diacrylate, 3-5 parts of hydroxyethyl methylacrylate, 0.1-0.3 part of a photoinitiator, 5-8 parts of silver nitrate, 55-65 parts of silver powder and 10-15 parts of ethyl acetate. Imidazole groups on the functionalized polyurethane can be complexed with silver ions in silver nitrate to form a silver organic framework, polyaniline and silver powder on the side chain of the functionalized polyurethane are matched, the conductivity of the material is guaranteed, meanwhile, unsaturated double bonds on the molecular chain of the functionalized polyurethane can be complexed with 1, 3-butanediol, and the conductivity of the material is improved. According to the conductive silver paste curing film, 1, 6-hexanediol diacrylate and hydroxyethyl methylacrylate are polymerized under the action of a photoinitiator to form a semi-interpenetrating grid structure, and meanwhile, polyhedral oligomeric silsesquioxane is coated to form a core-shell structure, so that the mechanical property of the conductive silver paste curing film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of printed conductive silver paste, and in particular to a low-temperature printed conductive silver paste and a preparation method thereof. Background Art

[0002] Conductive silver paste integrates electronics, chemical industry and metallurgy, and is the basic material of today's electronic technology industry. As materials continue to move towards lighter, thinner and more intelligent directions, it is urgent to develop high-performance, low-cost conductive silver paste to meet increasingly stringent development requirements. UV-curable conductive silver paste also has the characteristics of instant curing, high yield, significant shielding effect, low requirements for printed substrates, no need for high-temperature sintering, and simplifies traditional processes, which can greatly improve the competitiveness of electronic products. Due to the characteristics of the curing method, UV-curable silver paste will be increasingly used in advanced processes such as ultra-narrow connections, ultra-thin electrodes, and fast solderless mounting of electronic devices. According to current reports on UV-curable silver paste, due to the decrease in its mechanical properties due to the addition of silver powder, it is easy to break or increase resistance after multiple bending, which in turn affects normal use. Summary of the invention

[0003] The purpose of the present invention is to provide a low-temperature printed conductive silver paste and a preparation method thereof, so as to solve the problem that the low-temperature conductive silver paste has poor anti-bending effect at present.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a low-temperature printed conductive silver paste comprises the following steps: Step A1: polyethylene glycol, modified monomer, isophorone diisocyanate and DMF are uniformly mixed, and dibutyltin dilaurate is added under stirring at a speed of 120-150 r / min and a temperature of 40-50° C., and the mixture is reacted for 30-40 min, hydroxy-terminated polybutadiene is added, and the reaction is continued for 30-40 min, and 4-aminoimidazole is added, and the reaction is continued for 1-1.5 h to obtain a modified polyurethane; Step A2: uniformly mixing the modified polyurethane and DMF, stirring and adding ammonium persulfate and aniline at a speed of 60-80 r / min, a temperature of 10-15° C., and a pH value of 1-2, and reacting for 20-25 hours to obtain a functionalized polyurethane; Step A3: Weigh the following raw materials in parts by weight: 10-15 parts of functionalized polyurethane, 3-5 parts of 1,6-hexanediol diacrylate, 3-5 parts of hydroxyethyl methacrylate, 0.1-0.3 parts of photoinitiator, 5-8 parts of silver nitrate, 55-65 parts of silver powder and 10-15 parts of ethyl acetate, mix the raw materials evenly to prepare a low-temperature printing conductive silver paste.

[0005] Furthermore, the mass ratio of the polyethylene glycol, the modified monomer, isophorone diisocyanate, the hydroxy-terminated polybutadiene and the 4-aminoimidazole described in step A1 is 12:20:35:25:5, and the amount of dibutyltin dilaurate is 1% by mass of isophorone diisocyanate.

[0006] Furthermore, the mass ratio of the modified polyurethane and aniline in step A2 is 15:4, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0007] Further, the modified monomer is prepared by the following steps: Step B1: 4-hydroxyphthalic anhydride and DMF are mixed evenly, stirred and aniline is added at a speed of 120-150 r / min and a temperature of 0°C, and the reaction is carried out for 1-1.5 hours, the temperature is raised to 60-65°C, triethylamine, acetic anhydride and nickel acetate are added, and the reaction is continued for 2-3 hours to obtain intermediate 1, intermediate 1, allyl chloride, potassium carbonate and DMF are mixed evenly, and the reaction is carried out at a speed of 200-300 r / min and a temperature of 70-75°C for 10-15 hours to obtain intermediate 2; Step B2: The intermediate 2, 3-mercaptopropyltrimethoxysilane, benzophenone and DMF are mixed uniformly, and reacted for 5-7 hours at a speed of 120-150 r / min, a temperature of 20-25° C. and irradiation with 365 nm ultraviolet light to obtain the intermediate 3; the intermediate 3, isopropanol, sodium hydroxide and deionized water are mixed, and reacted for 3-5 hours at a speed of 150-200 r / min and a temperature of 85-90° C., and then cooled to 20-25° C. and reacted for 10-15 hours to obtain the functionalized cyclotetrasiloxane sodium tetrasiloxide; Step B3: functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, stirred and methyldichlorosilane is added at a speed of 150-200 r / min and a temperature of 0°C, and the reaction is carried out for 3-5 hours, and then the temperature is raised to 20-25°C and the reaction is carried out for 20-24 hours to obtain functionalized cage-type silsesquioxane; the functionalized cage-type silsesquioxane, allyl alcohol, chloroplatinic acid and DMF are mixed evenly, and the reaction is carried out at a speed of 120-150 r / min and a temperature of 70-80°C for 8-10 hours to obtain a modified monomer.

[0008] Furthermore, the amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate in step B1 is 50mmol:50mL:50mmol:5mL:12mL:3.5g, and the molar ratio of intermediate 1, allyl chloride and potassium carbonate is 1:1:1.1.

[0009] Furthermore, the molar ratio of the intermediate 2 and 3-mercaptopropyltrimethoxysilane described in step B2 is 1:1, the amount of benzophenone is 5‰ of the mass of 3-mercaptopropyltrimethoxysilane, and the amount ratio of intermediate 3, isopropanol, sodium hydroxide and deionized water is 6mmol:6mL:7mmol:4mmol.

[0010] Furthermore, the mass ratio of the functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and methyldichlorosilane described in step B3 is 15:4:30:3.5, the molar ratio of the functionalized cage-type silsesquioxane and allyl alcohol is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of allyl alcohol.

[0011] Beneficial effects of the present invention: A low-temperature printed conductive silver paste disclosed in the present application comprises the following raw materials: functionalized polyurethane, 1,6-hexanediol diacrylate, hydroxyethyl methacrylate, a photoinitiator, silver nitrate, silver powder and ethyl acetate; the functionalized polyurethane is reacted with polyethylene glycol, a modified monomer and isophorone diisocyanate to obtain a polyurethane prepolymer, which is then chain extended with terminal hydroxyl polybutadiene, and finally terminated with 4-aminoimidazole to obtain a modified polyurethane; the modified polyurethane is reacted with aniline to form a polyaniline segment on the side chain of the modified polyurethane to obtain a functionalized polyurethane.

[0012] The modified monomer uses 4-hydroxyphthalic anhydride and aniline as raw materials, so that the anhydride on the 4-hydroxyphthalic anhydride reacts with the amino group on the aniline to obtain intermediate 1, and the intermediate 1 is reacted with allyl chloride so that the hydroxyl group on the intermediate 1 reacts with the chlorine atom site on the allyl chloride to obtain intermediate 2, and the intermediate 2 is reacted with 3-mercaptopropyltrimethoxysilane so that the double bond on the intermediate 2 reacts with the mercapto group on the 3-mercaptopropyltrimethoxysilane to obtain intermediate The intermediate 3 is hydrolyzed and polycondensed to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide, the functionalized cyclotetrasiloxane sodium tetrasiloxide is reacted with methyldichlorosilane, so that the sodium siloxide on the functionalized cyclotetrasiloxane sodium tetrasiloxide reacts with the chlorine atom site on the methyldichlorosilane to obtain functionalized cage-type silsesquioxane, and the functionalized cage-type silsesquioxane is reacted with allyl alcohol, so that the Si-H bond on the functionalized cage-type silsesquioxane reacts with the double bond on the allyl alcohol to obtain a modified monomer.

[0013] During the curing process of the conductive silver paste, the imidazole groups on the functionalized polyurethane can complex with the silver ions in silver nitrate to form a silver organic framework, and cooperate with the polyaniline and silver powder on the side chain of the functionalized polyurethane to form a stable conductive path after the conductive silver paste is cured, thereby ensuring conductivity. At the same time, the unsaturated double bonds on the functionalized polyurethane molecular chain can polymerize with 1,6-hexanediol diacrylate and hydroxyethyl methacrylate under the action of a photoinitiator, forming a semi-interpenetrating grid structure with the polyaniline on the side chain, and at the same time being coated with cage-type silsesquioxane to form a core-shell structure, thereby improving the mechanical properties of the conductive silver paste cured film. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] Embodiment 1: A method for preparing a low-temperature printed conductive silver paste, comprising the following steps: Step A1: polyethylene glycol, modified monomer, isophorone diisocyanate and DMF are uniformly mixed, and dibutyltin dilaurate is added under stirring at a speed of 120 r / min and a temperature of 40° C., and the mixture is reacted for 30 min, hydroxy-terminated polybutadiene is added, and the reaction is continued for 30 min, and 4-aminoimidazole is added, and the reaction is continued for 1 h to obtain a modified polyurethane; Step A2: the modified polyurethane and DMF were mixed evenly, and under the conditions of a rotation speed of 60 r / min, a temperature of 10° C., and a pH value of 1, ammonium persulfate and aniline were added and reacted for 20 hours to obtain a functionalized polyurethane; Step A3: Weigh the following raw materials in parts by weight: 10 parts of functionalized polyurethane, 3 parts of 1,6-hexanediol diacrylate, 3 parts of hydroxyethyl methacrylate, 0.1 parts of photoinitiator, 5 parts of silver nitrate, 55 parts of silver powder and 10 parts of ethyl acetate, mix the raw materials evenly to prepare a low-temperature printing conductive silver paste.

[0016] The mass ratio of the polyethylene glycol, modified monomer, isophorone diisocyanate, hydroxy-terminated polybutadiene and 4-aminoimidazole described in step A1 is 12:20:35:25:5, the amount of dibutyltin dilaurate is 1% by mass of isophorone diisocyanate, the molecular weight of the polyethylene glycol is 2000, and the molecular weight of the hydroxy-terminated polybutadiene is 2000.

[0017] The mass ratio of the modified polyurethane and aniline in step A2 is 15:4, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0018] The photoinitiator described in step A3 is 819.

[0019] The modified monomer is prepared by the following steps: Step B1: 4-hydroxyphthalic anhydride and DMF were mixed evenly, stirred and aniline was added at a speed of 120 r / min and a temperature of 0°C, and the reaction was carried out for 1 hour, the temperature was raised to 60°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 2 hours to obtain intermediate 1, intermediate 1, allyl chloride, potassium carbonate and DMF were mixed evenly, and the reaction was carried out at a speed of 200 r / min and a temperature of 70°C for 10 hours to obtain intermediate 2; Step B2: The intermediate 2, 3-mercaptopropyltrimethoxysilane, benzophenone and DMF were mixed evenly, and reacted for 5 hours at a speed of 120 r / min, a temperature of 20° C. and irradiation with 365 nm ultraviolet light to obtain the intermediate 3. The intermediate 3, isopropanol, sodium hydroxide and deionized water were mixed, and reacted for 3 hours at a speed of 150 r / min and a temperature of 85° C., and then cooled to 20° C. and reacted for 10 hours to obtain the functionalized cyclotetrasiloxane sodium tetrasiloxide; Step B3: functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, stirred and methyldichlorosilane is added at a speed of 150 r / min and a temperature of 0°C, and the reaction is carried out for 3 hours, and then the temperature is raised to 20°C and the reaction is carried out for 20 hours to obtain functionalized cage-type silsesquioxane; the functionalized cage-type silsesquioxane, allyl alcohol, chloroplatinic acid and DMF are mixed evenly, and the reaction is carried out at a speed of 120 r / min and a temperature of 70°C for 8 hours to obtain a modified monomer.

[0020] The amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate in step B1 is 50mmol:50mL:50mmol:5mL:12mL:3.5g, and the molar ratio of intermediate 1, allyl chloride and potassium carbonate is 1:1:1.1.

[0021] The molar ratio of intermediate 2 and 3-mercaptopropyltrimethoxysilane described in step B2 is 1:1, the amount of benzophenone used is 5‰ of the mass of 3-mercaptopropyltrimethoxysilane, and the amount ratio of intermediate 3, isopropanol, sodium hydroxide and deionized water is 6mmol:6mL:7mmol:4mmol.

[0022] The mass ratio of the functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and methyldichlorosilane described in step B3 is 15:4:30:3.5, the molar ratio of the functionalized cage-type silsesquioxane and allyl alcohol is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of allyl alcohol.

[0023] Embodiment 2: A method for preparing a low-temperature printed conductive silver paste, comprising the following steps: Step A1: polyethylene glycol, modified monomer, isophorone diisocyanate and DMF are uniformly mixed, and dibutyltin dilaurate is added under stirring at a speed of 120 r / min and a temperature of 45° C., and the mixture is reacted for 35 min, hydroxy-terminated polybutadiene is added, and the reaction is continued for 35 min, and 4-aminoimidazole is added, and the reaction is continued for 1.5 h to obtain a modified polyurethane; Step A2: the modified polyurethane and DMF were mixed evenly, and ammonium persulfate and aniline were added under stirring at a speed of 60 r / min, a temperature of 15° C., and a pH value of 1.5, and the mixture was reacted for 25 hours to obtain a functionalized polyurethane; Step A3: Weigh the following raw materials in parts by weight: 13 parts of functionalized polyurethane, 4 parts of 1,6-hexanediol diacrylate, 4 parts of hydroxyethyl methacrylate, 0.2 parts of photoinitiator, 6 parts of silver nitrate, 60 parts of silver powder and 13 parts of ethyl acetate, mix the raw materials evenly to prepare a low-temperature printing conductive silver paste.

[0024] The mass ratio of the polyethylene glycol, modified monomer, isophorone diisocyanate, hydroxy-terminated polybutadiene and 4-aminoimidazole described in step A1 is 12:20:35:25:5, the amount of dibutyltin dilaurate is 1% by mass of isophorone diisocyanate, the molecular weight of the polyethylene glycol is 2000, and the molecular weight of the hydroxy-terminated polybutadiene is 2000.

[0025] The mass ratio of the modified polyurethane and aniline in step A2 is 15:4, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0026] The photoinitiator described in step A3 is 1173.

[0027] The modified monomer is prepared by the following steps: Step B1: 4-hydroxyphthalic anhydride and DMF were mixed evenly, stirred and aniline was added at a speed of 120 r / min and a temperature of 0°C, and the reaction was carried out for 1.5 hours, the temperature was raised to 60°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 3 hours to obtain intermediate 1, intermediate 1, allyl chloride, potassium carbonate and DMF were mixed evenly, and the reaction was carried out at a speed of 200 r / min and a temperature of 75°C for 10 hours to obtain intermediate 2; Step B2: The intermediate 2, 3-mercaptopropyltrimethoxysilane, benzophenone and DMF were mixed evenly, and the mixture was reacted for 6 hours at a speed of 120 r / min, a temperature of 25° C. and irradiation with 365 nm ultraviolet light to obtain the intermediate 3. The intermediate 3, isopropanol, sodium hydroxide and deionized water were mixed, and the mixture was reacted for 4 hours at a speed of 150 r / min and a temperature of 90° C., and then the mixture was cooled to 25° C. and reacted for 10 hours to obtain the functionalized sodium cyclotetrasiloxane tetrasiloxide; Step B3: functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, stirred and methyldichlorosilane is added at a speed of 200 r / min and a temperature of 0°C, and the reaction is carried out for 4 hours, and then the temperature is raised to 25°C and the reaction is carried out for 20 hours to obtain functionalized cage-type silsesquioxane; the functionalized cage-type silsesquioxane, allyl alcohol, chloroplatinic acid and DMF are mixed evenly, and the reaction is carried out at a speed of 150 r / min and a temperature of 75°C for 9 hours to obtain a modified monomer.

[0028] The amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate in step B1 is 50mmol:50mL:50mmol:5mL:12mL:3.5g, and the molar ratio of intermediate 1, allyl chloride and potassium carbonate is 1:1:1.1.

[0029] The molar ratio of intermediate 2 and 3-mercaptopropyltrimethoxysilane described in step B2 is 1:1, the amount of benzophenone used is 5‰ of the mass of 3-mercaptopropyltrimethoxysilane, and the amount ratio of intermediate 3, isopropanol, sodium hydroxide and deionized water is 6mmol:6mL:7mmol:4mmol.

[0030] The mass ratio of the functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and methyldichlorosilane described in step B3 is 15:4:30:3.5, the molar ratio of the functionalized cage-type silsesquioxane and allyl alcohol is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of allyl alcohol.

[0031] Embodiment 3: A method for preparing a low-temperature printed conductive silver paste, comprising the following steps: Step A1: polyethylene glycol, modified monomer, isophorone diisocyanate and DMF are uniformly mixed, and dibutyltin dilaurate is added under stirring at a speed of 150 r / min and a temperature of 50° C., and the mixture is reacted for 40 min. hydroxy-terminated polybutadiene is added, and the reaction is continued for 40 min. 4-aminoimidazole is added, and the reaction is continued for 1.5 h to obtain a modified polyurethane. Step A2: the modified polyurethane and DMF were mixed evenly, and under the conditions of a rotation speed of 80 r / min, a temperature of 15° C., and a pH value of 2, ammonium persulfate and aniline were added and reacted for 25 hours to obtain a functionalized polyurethane; Step A3: Weigh the following raw materials in parts by weight: 15 parts of functionalized polyurethane, 5 parts of 1,6-hexanediol diacrylate, 5 parts of hydroxyethyl methacrylate, 0.3 parts of photoinitiator, 8 parts of silver nitrate, 65 parts of silver powder and 15 parts of ethyl acetate, mix the raw materials evenly to prepare a low-temperature printing conductive silver paste.

[0032] The mass ratio of the polyethylene glycol, modified monomer, isophorone diisocyanate, hydroxy-terminated polybutadiene and 4-aminoimidazole described in step A1 is 12:20:35:25:5, the amount of dibutyltin dilaurate is 1% by mass of isophorone diisocyanate, the molecular weight of the polyethylene glycol is 2000, and the molecular weight of the hydroxy-terminated polybutadiene is 2000.

[0033] The mass ratio of the modified polyurethane and aniline in step A2 is 15:4, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0034] The photoinitiator described in step A3 is 2959.

[0035] The modified monomer is prepared by the following steps: Step B1: 4-hydroxyphthalic anhydride and DMF were mixed evenly, stirred and aniline was added at a speed of 150 r / min and a temperature of 0°C, and the reaction was carried out for 1.5 hours, the temperature was raised to 65°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 3 hours to obtain intermediate 1, intermediate 1, allyl chloride, potassium carbonate and DMF were mixed evenly, and the reaction was carried out at a speed of 300 r / min and a temperature of 75°C for 15 hours to obtain intermediate 2; Step B2: The intermediate 2, 3-mercaptopropyltrimethoxysilane, benzophenone and DMF were mixed evenly, and the mixture was reacted for 7 hours at a speed of 150 r / min, a temperature of 25° C. and irradiation with 365 nm ultraviolet light to obtain the intermediate 3. The intermediate 3, isopropanol, sodium hydroxide and deionized water were mixed, and the mixture was reacted for 5 hours at a speed of 200 r / min and a temperature of 90° C., and then the mixture was cooled to 25° C. and reacted for 15 hours to obtain the functionalized sodium cyclotetrasiloxane tetrasiloxide; Step B3: functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, stirred and methyldichlorosilane is added at a speed of 200 r / min and a temperature of 0°C, and the reaction is carried out for 5 hours, and then the temperature is raised to 25°C and the reaction is carried out for 24 hours to obtain functionalized cage-type silsesquioxane; the functionalized cage-type silsesquioxane, allyl alcohol, chloroplatinic acid and DMF are mixed evenly, and the reaction is carried out at a speed of 150 r / min and a temperature of 80°C for 10 hours to obtain a modified monomer.

[0036] The amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate in step B1 is 50mmol:50mL:50mmol:5mL:12mL:3.5g, and the molar ratio of intermediate 1, allyl chloride and potassium carbonate is 1:1:1.1.

[0037] The molar ratio of intermediate 2 and 3-mercaptopropyltrimethoxysilane described in step B2 is 1:1, the amount of benzophenone used is 5‰ of the mass of 3-mercaptopropyltrimethoxysilane, and the amount ratio of intermediate 3, isopropanol, sodium hydroxide and deionized water is 6mmol:6mL:7mmol:4mmol.

[0038] The mass ratio of the functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and methyldichlorosilane described in step B3 is 15:4:30:3.5, the molar ratio of the functionalized cage-type silsesquioxane and allyl alcohol is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of allyl alcohol.

[0039] Comparative Example 1: Compared with Example 1, no silver nitrate was added to this comparative example, and the remaining steps were the same.

[0040] Comparative Example 2: Compared with Example 1, this comparative example uses modified polyurethane instead of functional polyurethane, and the other steps are the same.

[0041] Comparative Example 3: Compared with Example 1, no modified monomer was added to this comparative example, and the remaining steps were the same.

[0042] The conductive silver paste prepared in Examples 1-3 and Comparative Examples 1-3 was brushed onto a PET film with a thickness of 50 μm, and irradiated for 30 seconds under 365 nm ultraviolet light to obtain a sample. The sample was tested for resistivity using an RTS-8 four-probe tester. The conductive silver paste was made into a wire with a width of 1 mm and a length of 100 mm, the wire was symmetrically bent 180°, a weight was pressed on the wire with a pressure of 5.5 kPa, and the pressure was maintained for 1 min. The wire was then bent 180° in the opposite direction and maintained for 1 min. The bending was repeated 10 times, and the resistivity decrease rate was detected. The test results are shown in Table 1 below.

[0043] Table 1 It can be seen from Table 1 above that the present application has good conductivity and anti-bending effects.

[0044] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature printed conductive silver paste, characterized in that: The specific steps include: Step A1: polyethylene glycol, a modified monomer, isophorone diisocyanate and DMF are mixed and stirred, and dibutyltin dilaurate is added to react, terminal hydroxyl polybutadiene is added, the reaction is continued, and 4-aminoimidazole is added, and the reaction is continued to obtain a modified polyurethane; Step A2: mixing and stirring the modified polyurethane and DMF, and adding ammonium persulfate and aniline to react to obtain a functionalized polyurethane; Step A3: Weigh the following raw materials in parts by weight: 10-15 parts of functionalized polyurethane, 3-5 parts of 1,6-hexanediol diacrylate, 3-5 parts of hydroxyethyl methacrylate, 0.1-0.3 parts of photoinitiator, 5-8 parts of silver nitrate, 55-65 parts of silver powder and 10-15 parts of ethyl acetate, mix the raw materials evenly to prepare a low-temperature printing conductive silver paste.

2. The method for preparing a low-temperature printed conductive silver paste according to claim 1, characterized in that: The amount ratio of the polyethylene glycol, the modified monomer, isophorone diisocyanate, the hydroxy-terminated polybutadiene and 4-aminoimidazole described in step A1 is 12:20:35:25:

5.

3. The method for preparing a low-temperature printed conductive silver paste according to claim 1, characterized in that: The mass ratio of the modified polyurethane and aniline described in step A2 is 15:

4.

4. The method for preparing a low-temperature printed conductive silver paste according to claim 1, characterized in that: The modified monomer is prepared by the following steps: Step B1: 4-hydroxyphthalic anhydride and DMF are mixed and stirred, and aniline is added to react, the temperature is increased, and triethylamine, acetic anhydride and nickel acetate are added to continue the reaction to obtain intermediate 1, and intermediate 1, allyl chloride, potassium carbonate and DMF are mixed and reacted to obtain intermediate 2; Step B2: intermediate 2, 3-mercaptopropyltrimethoxysilane, benzophenone and DMF are mixed to react to obtain intermediate 3, intermediate 3, isopropanol, sodium hydroxide and deionized water are mixed to react, and the temperature is lowered to continue the reaction to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide; Step B3: functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed and stirred, and methyldichlorosilane is added to react, and then the temperature is increased to continue the reaction to obtain functionalized cage-type silsesquioxane. The functionalized cage-type silsesquioxane, allyl alcohol, chloroplatinic acid and DMF are mixed and reacted to obtain a modified monomer.

5. The method for preparing a low-temperature printed conductive silver paste according to claim 4, characterized in that: The amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate in step B1 is 50mmol:50mL:50mmol:5mL:12mL:3.5g, and the molar ratio of intermediate 1, allyl chloride and potassium carbonate is 1:1:1.

1.

6. The method for preparing a low-temperature printed conductive silver paste according to claim 4, characterized in that: The molar ratio of intermediate 2 and 3-mercaptopropyltrimethoxysilane in step B2 is 1:1, and the amount ratio of intermediate 3, isopropanol, sodium hydroxide and deionized water is 6mmol:6mL:7mmol:4mmol.

7. The method for preparing a low-temperature printed conductive silver paste according to claim 4, characterized in that: The mass ratio of the functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and methyldichlorosilane described in step B3 is 15:4:30:3.5, and the molar ratio of the functionalized cage-type silsesquioxane and allyl alcohol is 1:

2.

8. A low temperature printed conductive silver paste, characterized in that: Prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Conductive paste and conductive film

    CN105874542A

  • Polyurethane adhesive for battery electrode material and preparation method thereof

    CN115911392A

  • Polyurethane-cationic polymer emulsion with interpenetrating network structure, preparation method and application of polyurethane-cationic polymer emulsion in field of personal care

    CN116003696A

  • Anti-cracking aerogel coating and preparation method thereof

    CN116218448A

  • Conductive paste, and method of manufacturing wiring board using it

    JP2007184213A